STUDI PERILAKU MAKAN GAJAH SUMATERA (Elephas maximus sumatranus) PADA INDUK DAN ANAK GAJAH DI Elepant Respon Unit (ERU) TEGAL YOSOTAMAN NASIONAL WAY KAMBAS - Reki Hamdani; Gunardi Djoko Winarno; Arif Darmawan; Sugeng P. Harianto (Jurnal Hutan Tropis, 2021)
The Sumatran Elephant (Elephas maximus Sumatranus) has a large body causing the elephant to require very much feed. Age and weight affect the need for the number of parent and child feed. Eating behaviors both in the cage and in the wild include the movement of picking, cutting and chewing. Knowledge of the proportion of the eating behavior of parents and children of elephants will be useful as a reference in the efforts to preserve the Sumatran elephant population in both Insitu and exsitu conservation activities. The aim of the study is to determine the proportion of the daily eating behavior of Sumatran elephants for 24 hours. The research was held in April 2019 at the Elephant response Unit (ERU) Tegal Yoso National Park Way Kambas. The method used is a sampling scan method by calculating the average and percentage values that are in use Microsoft Excel 2007 which will be displayed in the form of graphs and analyses in a descriptive. The results of research data showed that the percentage of behavior is greater than the parent in comparison of children (42.24%) and (28%) With feed that is in the can of natural feed or condensuration and additional feed in the cage. The proportion of feeding to two elephants in the morning to late afternoon (53.93%) Parent and (42.59%) Children. Furthermore, in the afternoon until the morning of the day (30.55%) Parent and (13.42%) Children.